Psychological autopsy of male perpetrator and female victim intimate partner murder-suicide in a rural community in Limpopo Province - Muthivhi, Elelwani (My University, 2021)
Though it is difficult to determine the prevalence of intimate partner murder-suicide (IPMS), it does appear that this phenomenon is reported in different parts of the world. The psychological consequences of this phenomenon to the surviving family members have also been widely reported. The aim of the study was to conduct a psychological autopsy (PA) on male perpetrators and female victims of IPMS in a rural community in Limpopo Province. The research objectives were; 1) To understand the psychological intent, motives and behaviour of male perpetrators and female victims in IPMS; 2) to identify role played by male perpetrators and female victims in effecting their death; 3) To investigate multiple trajectories (that is, psychological, social, environmental and cultural/historical context) contributed to IPMS; 4) To identify other factors or events that may have triggered fatal behaviour of both male perpetrators and female victims of IPMS; 5) To understand circumstances around IPMS; 6) To develop guidelines to assist in responding to IPMS. The study was qualitative in nature. In particular, the case study design was used. Interpretative phenomenology approach was adopted. The study was informed by the Theory of Planned Behaviour. Purposive sampling used to select cases of intimate partner murder-suicide. Snowball sampling used to select participants and archival sampling was used to select archived record. Thematic Content Analysis (that is, inductive analysis) was used to identify patterns of meaning across the datasets in order to provide answers to the research objective. The research revealed five major themes. These themes are psychological profile of perpetrators, psychological profile of victims, multiple trajectories towards IPMS, possible triggers in IPMS and circumstance around IPMS. Research findings suggest that although IPMS came as a total surprise there were psychological intent, motive, behaviour on the part of male perpetrators and female victims. The study recommends the need for further PA studies to shed the light on the psychological intent of male perpetrators and female victims of IPMS. The psychological intent of male perpetrators and female victims of IPMS heighten the urgency for policy makers to develop IPMS prevention strategies and policies
Thesis (Ph.D. (Psychology)) -- University of Limpopo, 2021
Keywords: Intimate partner violence; Muder-suicide; Psychological autopsy; Criminal investigation; Suicide; Psychological autopsy; Murder-suicide